2021
DOI: 10.1111/joes.12475
|View full text |Cite
|
Sign up to set email alerts
|

Measuring intangible assets—A review of the state of the art

Abstract: This paper presents an overview of the state of the art in the field surrounding the measurement of “intangibles” for productivity analysis. The purpose of the paper is to inform indicator development and implementation in economic analysis, both at the micro and aggregated levels. The review seeks to capture the development of intangibles measurement, which has explored a variety of directions, both in terms of definition, method and data. We characterize both the diversity of the field and its development ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…There are varied efforts to measure intangible values. Van Criekingen et al [9] identified six different approaches to measuring intangible assets, which include the Corrado et al [8] expenditures-based approach, the survey-based measurement of expenditures approach, the measurement based on firm balance sheet data, occupation or task-based approach, intellectual property rights-based measures and market valuation approach. The expenditures-based approach of Corrado et al, [8] provides a macroeconomic framework that measures intangible assets.…”
Section: Concept Of Intangibles and Intellectual Capitalmentioning
confidence: 99%
See 4 more Smart Citations
“…There are varied efforts to measure intangible values. Van Criekingen et al [9] identified six different approaches to measuring intangible assets, which include the Corrado et al [8] expenditures-based approach, the survey-based measurement of expenditures approach, the measurement based on firm balance sheet data, occupation or task-based approach, intellectual property rights-based measures and market valuation approach. The expenditures-based approach of Corrado et al, [8] provides a macroeconomic framework that measures intangible assets.…”
Section: Concept Of Intangibles and Intellectual Capitalmentioning
confidence: 99%
“…The expenditures-based approach of Corrado et al, [8] provides a macroeconomic framework that measures intangible assets. They categorized the intangible assets into three groups, namely, economic competencies, innovative property and computerized information [9,26]. The second is the survey-based measurement of expenditures with the aim to use survey instruments to measure the investments in intangibles.…”
Section: Concept Of Intangibles and Intellectual Capitalmentioning
confidence: 99%
See 3 more Smart Citations